The role of short-time work and discretionary policy measures in mitigating the effects of the COVID-19 crisis in Germany - Michael Christl; Silvia De Poli; Tine Hufkens; Andreas Peichl; Mattia Ricci (European Commission, Joint Research Centre (JRC), 2021)
In this paper, we investigate the impact of the COVID-19 pandemic on German household income using a micro-level approach. We combine a microsimulation model with labour market transition techniques to simulate the COVID-19 shock on the German labour market. We find the consequences of the labour market shock to be highly regressive with a strong impact on the poorest households. However, this effect is nearly entirely offset by automatic stabilisers and discretionary policy measures. We explore the cushioning effect of these policies in detail, showing that short-time working schemes and especially the one-off payments for children are effective in cushioning the income loss of the poor.
Keywords: D31; E24; H24; 330; COVID-19; EUROMOD; microsimulation; STW; automatic stabilisers